2018
DOI: 10.1136/bmjopen-2018-023676
|View full text |Cite
|
Sign up to set email alerts
|

How is the audit of therapy intensity influencing rehabilitation in inpatient stroke units in the UK? An ethnographic study

Abstract: ObjectivesOccupational therapy, physiotherapy and speech and language therapy are central to rehabilitation after a stroke. The UK has introduced an audited performance target: that 45 min of each therapy should be provided to patients deemed appropriate. We sought to understand how this has influenced delivery of stroke unit therapy.DesignEthnographic study, including observation and interviews. The theoretical framework drew on the work of Lipsky and Power, framing therapists as ‘street level bureaucrats’ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 36 publications
1
41
0
2
Order By: Relevance
“…It could also indicate, as observed by others, that therapists may have overreported or struggled to accurately recall the actual time spent on treatment 31. However, the differences in findings between studies might reflect different interpretations as to what upper limb therapy actually comprises in this study as some therapists may have considered the time to include activities where the upper limb was likely to benefit from therapy, but was not the direct target of intervention (eg, aerobic exercise) 32 33. This ambiguity might be an inevitable limitation of the current study’s findings, but focus on content of therapy and who delivered it attempted to minimise this effect by providing some guidance to therapists on what did, and what did not, constitute therapy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It could also indicate, as observed by others, that therapists may have overreported or struggled to accurately recall the actual time spent on treatment 31. However, the differences in findings between studies might reflect different interpretations as to what upper limb therapy actually comprises in this study as some therapists may have considered the time to include activities where the upper limb was likely to benefit from therapy, but was not the direct target of intervention (eg, aerobic exercise) 32 33. This ambiguity might be an inevitable limitation of the current study’s findings, but focus on content of therapy and who delivered it attempted to minimise this effect by providing some guidance to therapists on what did, and what did not, constitute therapy.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to research trials, large improvements in upper limb functioning have been reported in a NHS-funded clinical service (the Queen’s Square Upper Limb Programme) that delivers 90 hours of multidisciplinary upper limb rehabilitation over 3 weeks 33. When the intensities of therapy in these studies are compared with those measured in observational studies,32 39 SSNAP data8 and the current study, they emphasise that service provision for rehabilitation of the upper limb after stroke needs radical alteration if it is to empower therapists to provide effective therapy and maximise recovery for people after stroke. Further research is therefore urgently needed to find ways to upscale services so that they can deliver greater intensities of high-quality, personalised, evidence-based therapy for the upper limb in clinical practice.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, therapy is rarely a 7-day service; in 2016, SSNAP data showed that only 31% of stroke units had access to at least two types of therapy 7 days per week. 35 Several authors have stated concerns about the focus on a 45-minute therapy guideline: 11,12 first, the accuracy of reporting and what is being counted and, second, that direct contact time with therapists could be considerably lower. Clarke et al 11 carried out an ethnographic case study across eight stroke units comprising > 1000 hours of non-participant observations and 433 patient-specific therapy observations and found that a considerable amount of time was spent carrying out activities relating to information exchange rather than patient-focused therapy.…”
Section: Rehabilitation Recovery and Persistent Concernsmentioning
confidence: 99%
“…Clarke et al 11 carried out an ethnographic case study across eight stroke units comprising > 1000 hours of non-participant observations and 433 patient-specific therapy observations and found that a considerable amount of time was spent carrying out activities relating to information exchange rather than patient-focused therapy. In another ethnographic study across three stroke units, Taylor et al 12 found that therapists wanted to provide more therapy and felt guilty for not doing so; there was also a lack of multidisciplinary rehabilitation. Both research teams found that rehabilitation was largely the responsibility of therapists, and patients were often observed as inactive outside their designated therapy sessions.…”
Section: Rehabilitation Recovery and Persistent Concernsmentioning
confidence: 99%
See 1 more Smart Citation